Perbedaan Komposisi Famili Kupu-Kupu (Papilionoideae) di Kawasan Cagar Alam Gunung Tilu Ciwidey Bandung - Ruslan, Hasni; Amirah, Karina Mutiara; Kusuma Putra, Adhiya Nabhan; Wahyuningsih, Endang (Seminar Nasional Lahan Suboptimal, 2024)
Ruslan, H., Wahyuningsih, E., Amirah, K. M., & Putra, A. N. K. (2024). Differences in the composition of the butterfly family (Papilionoideae) in the Mount Tilu Ciwidey Bandung Nature Reserve Area. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 59–68). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Butterflies have an important role in nature, having high sensitivity to environmental conditions. Research on butterflies in the Gunung Tilu Ciwidey Bandung Nature Reserve Area is still little published. The aimed of this research was to determine differences in the composition of butterfly families on tea and coffee plantations. The research was conducted on 1 – 5 May 2024 in tea gardens and coffee plantations. Observations were carried out at 08.00 – 12.00 WIB, and 13.00 – 16.00. The observation method is exploration. The results of research in two habitats found five families of butterflies in tea and coffee plantations: Nymphalidae, Papilionidae, Lycaenidae, Pieridae, and Riodinidae. More species from the Lycaenidae family are found on tea plantations. The number of butterfly species found in both habitats from the Nymphalidae and Papilionidae families is the same. The number of species of the Pieridae family is higher in coffee plantations than in tea gardens, and the Rionidae family is only found in coffee plantations. The existence of this butterfly family is influenced by host plants and food plants. Butterfly species from the Lycaenidae family found on tea and coffee plantations: Jamides pura, Nacaduba sp, Udara akasa. Butterfly species from the Nymphalidae family found on tea and coffee plantations: Lethe confusa, Melanitis leda, Mycalesis sp, Rohana parisatis javanica, Ypthima pandocus, Dolestilia bisaltidae. Butterfly species from the Papilionidae family found on tea and coffee plantations: Graphium sarpedon, Graphium doson, Pappilio memnon, Pappilio demolion. Butterfly species from the Pieridae family found on tea and coffee plantations: Delias hyperete, Delias belisama, Eurema hecabe, Eurema sari, Eurema blanda.